Hubungan Kualitas Tidur Dengan Keluhan Gangguan Muskuloskeletal Mahasiswa Stikes Flora Tingkat Akhir - Heni Triana; Rina Ramadani Sidabutar; Budiana Yazid (Jurnal Kesehatan Bhakti Husada, 2026)
Background: Nursing students often spend considerable time engaged with electronic screens, a habit believed to contribute to declining sleep quality. Continuous gadget use over extended periods may also trigger nervous system tension along with neck and shoulder pain, which in turn further disrupts nighttime rest. Methods: A cross-sectional design was applied involving 92 nursing students from the 2025 cohort at STIKes Flora, of whom 77 met the established inclusion and exclusion criteria. The Pittsburgh Sleep Quality Index was used to evaluate sleep quality, while the Nordic Body Map captured musculoskeletal complaints; both were distributed online via Google Form. Data processing proceeded through univariate and bivariate stages, employing Spearman Rank correlation in SPSS. Results: Findings show that more than half of respondents, namely 59.7% (n=46), experienced poor sleep quality. Regarding musculoskeletal complaints, 92.2% (n=71) reported no notable symptoms, while 7.8% (n=6) reported mild ones. The Spearman Rank test revealed a meaningful link between the two variables (p=0.037; r=0.239), although the strength of the relationship was weak and positive in direction. Conclusion: Sleep quality and musculoskeletal complaints among final-year nursing students at STIKes Flora proved to be statistically related, albeit weakly. Improving posture, limiting screen time, and maintaining disciplined sleep schedules are recommended as key measures to prevent future musculoskeletal problems. Keywords: sleep quality, musculoskeletal disorders, posture, nursing students, Nordic Body Map